Scientific Studies of the Qur’ān in the Contemporary Era: An Analysis of Concept, History, and Methodology - Amir, Selamat; Norasid, Muhamad Alihanafiah; Hilmi, Ahmad Bazli Ahmad (Journal of Islamic Thought and Civilization, 2023)
Significant efforts are made to revive scientific thinking,to require coordination through the application of the holistic elements of al-Qur’ān's scientific thinking. Therefore, methods in the scientific research of the Qur’ān were adapted according to the times and the development of civilizations. Hence, the current scientific study of the Qur’ān focused on the historiography to see its overall development. This study discussed the concept of scientific thought of the Qur’ān and its importance to the I‘jāz of the Qur’ān. Additionaly, the scholars’ position in emphasizing the scientific study of the Qur’ān was also presented in this research. Moreover, the adopted method of analysis was library research, which examined the relevant written research materials. The analysis illustrated that the Qur’ānic scientific methodology included divine science based on the I‘jāz al-Ilāhī, social science based on the I‘jāz al-Tashrī‘ī,and natural science based on the I‘jāz al-‘Ilmī and the development history offered comparisons of thoughts, which emerged during the Islamic civilization. Such Qur’ānic scientific methodology has led/conducted a deeper understanding of the Qur’ān and brought its study/interpretations to the public. Thus, this study is significant for exhibiting the importance of deepening the conceptual connection developed in the Qur’ānic scientific study with its historical development. This is to enable the application of epistemological thinking through scientific thinking in fulfilling human needs and the universal universe carefully and harmoniously.